PROFILE OF ENVIRONMENTAL LITERACY DISPOSITION INVENTORY (ELDI) STUDENTS OF PONTIANAK STATE HIGH SCHOOLS - Syavira Indriyani; A Afandi; Eko Sri Wahyuni (Jurnal Pelita Pendidikan, 2022)
Environmental literacy is needed to create a society that cares about the environment and as an effort to overcome environmental problems. This study aims to determine the environmental literacy profile of Class X State Senior High School students in Pontianak and to determine the relationship between the domain and environmental literacy. The subject of this research is the students of SMA Negeri in Pontianak City totalling 356 students who are determined by cluster sampling. The instrument used in this study was the form of a questionnaire with 37 statements and a test with 16 multiple-choice questions. This research method is descriptive quantitative. The results of this study indicate that the domains of attitudes towards the environment and behaviour towards the environment get “good” categories with an average value of 67.89 and 65.42 respectively. Meanwhile, the domains of environmental awareness and environmental knowledge get a sufficient category with an average value of 58.29 and 57.45 respectively. Environmental literacy based on indicators, it is categorized as “good” and sufficient. The correlation test results obtained indicate that each domain of environmental literacy has a relationship with environmental literacy.